A rare cause of small bowel obstruction - Peker, Elif; Erden, Ayşe; Erden, İlhan; Törüner, Murat (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Peker E, Erden A, Erden İ, Törüner M. A rare cause of small bowel obstruction. Turk J Gastroenterol 2018; 29: 237-8.